High stability bilayered perovskites through crystallization driven self-assembly - Koh, Teck Ming (2020)
In this manuscript we reveal the formation of bilayered hybrid perovskites of a new lower dimensional perovskite family, (CHMA)2(MA)n-1PbnI3 with n = 1-5, with high ambient stability via its crystallization driven self-assembly process. The spun-coated perovskite solution tends to crystallize and undergo phase separation during annealing, resulting in the formation of 2D/3D bilayered hybrid perovskites. Remarkably, this 2D/3D hybrid perovskites possess striking moisture resistance and displays high ambient stability up to 65 days. The bilayered approach in combining 3D and 2D perovskites could lead to a new era of perovskite research for high-efficiency photovoltaics with outstanding stability, with the 3D perovskite providing excellent electronic properties while the 2D perovskite endows it moisture stability.